Location Based Services and TeleCartography - Gartner, Georg; Cartwright, William; Peterson, Michael P. (Lecture Notes in Geoinformation and Cartography,, 2007)
This book provides for the first time a general overview of research activities related to location and map-based services. These activities have emerged over the last years, especially around issues of positioning, spatial modelling, cartographic communication as well as in the fields of ubiquitious cartography, geo-pervasive services, user-centered modelling and geo-wiki activities. The innovative and contemporary character of these topics has lead to a great variety of interdisciplinary contributions, from academia to business, from computer science to geodesy. Topics cover an enormous range with heterogenous relationships to the main book issues. Whilst contemporary cartography aims at looking at new and efficient ways for communicating spatial information the development and availability of technologies like mobile networking, mobile devices or short-range sensors lead to interesting new possibilities for achieving this aim. By trying to make use of available technologies, cartography and a variety of related disciplines look specifically at user-centered and conte- aware system development, as well as new forms of supporting wayfinding and navigation systems. Contributions are provided in five main sections and they cover all of these aspects and give a picture of the new and expanding field of Location Based Services and TeleCartography. Georg Gartner, Vienna, Austria William Cartwright, Melbourne, Australia Michael Peterson, Omaha, USA Table of Contents Georg Gartner LBS and TeleCartography: About the book. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 1 A series of Symposiums on LBS and TeleCartography. . . . . . . . . . . . . . . . . . . . . . 1 2 Progression of Research . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 3 2. 1 Terms. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 3 2. 2 Elements. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 4 3 Structure of the book . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .